BASIC CONCEPTS OF EDUCATIONAL MANAGEMENT - Nurcahya, Alsri; Hayatunnisa, St.; Zohriah, Anis; Firdaos, Rijal (LPPM Universitas Malikussaleh, 2024)
Management Education is a discipline that integrates the principles of management with the context of education. The basic concepts of education management include planning, organization, guidance, coordination, and control. This research aims to learn about the urgency of education management, the function of educational management, the management model in education, the principles of management education, the development of management theory, and the issues of education management. The method used in this research is qualitative research with a library research approach. In this case, the author carries out a collection of literature related to the basic concepts of education management. The result of this research is to know the urgency of the basic concepts and foundations of education management, as well as have a deeper understanding of the functions of education management, understand the management model in education, the principles of management education, describe the development of management theory, and understand the issues of educational management.